2022
DOI: 10.1007/s11187-022-00660-3
|View full text |Cite
|
Sign up to set email alerts
|

Power and entrepreneurship

Abstract: Entrepreneurship research has benefited from embracing three economic sociology lenses—networks, cognition, and institutions—but has treated power mainly implicitly. This paper pioneers how the concept of power can advance research into entrepreneurship. We illustrate how state actors, legacy firms, and entrepreneurs variously exert coercive, persuasive, and authoritative forms of power over entrepreneurial opportunities or exercise power to pursue them as free actors. We explicitly link context and opportunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 135 publications
1
9
0
1
Order By: Relevance
“…The study supports the works of Doces (2020) and Saha and Sen (2021) who empirically showed that democracy improves economic performance. This result is consistent with the findings of Acemoglu et al (2019) and the recent study by Farè et al (2023). These authors provided evidence that democracy has a positive impact on economic activities and that a democratised society encourages choices in business venturing and contributes to improvement in entrepreneurial behaviour (Knutsen, 2021).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The study supports the works of Doces (2020) and Saha and Sen (2021) who empirically showed that democracy improves economic performance. This result is consistent with the findings of Acemoglu et al (2019) and the recent study by Farè et al (2023). These authors provided evidence that democracy has a positive impact on economic activities and that a democratised society encourages choices in business venturing and contributes to improvement in entrepreneurial behaviour (Knutsen, 2021).…”
Section: Resultssupporting
confidence: 94%
“…Lehne et al (2014) opine that the political regime is an important determinant of institutions (Adserà & Boix, 2008). Political competition, as well as checks and balances embedded in a truly democratic system of government, reduce the tendencies of the government and entrepreneurs to exhibit rent-seeking behaviour (Farè et al, 2023; Goel & Nelson, 2021a). The public accountability element of democracy also creates transparency and makes the entrepreneurial environment friendly (Ajide, 2019; Olson, 2000).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Therefore, the role of each implementing partner agreeing with the importance of GESI is expected to determine the best reflective and flexible solutions. This shows that entrepreneurial reports have pragmatically been very fruitful, as well as embrace the lens of economics, networks, cognition, and institutional sociology, although the role of power is still implicit (Audretsch & Fiedler, 2022). The relationship between green entrepreneurship theory, institutions, and sustainable development is also academically considered to be well established (Mishra et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of SME owners and entrepreneurs, this can be particularly challenging as by their nature many elites of this type are skilled negotiators who expect to be able to shape and influence social interactions (Artinger et al. , 2015; Audretsch and Fiedler, 2023). Critical reflection and discussions within the research team or with senior fellow academics may help preserving a distant position and applying a similar interview style throughout all the interview situations, can be seen as helpful strategies.…”
Section: Methodological Considerations and Findings In Relation To In...mentioning
confidence: 99%
“…The very nature of elites, for instance, their ability to be confident speakers (Stephens, 2007) or more generally their confidence, as they are used to the fact that their views and thoughts usually matter in the lives of other people (Ostrander, 1993) as well as the possibility of a power difference (Mikecz, 2012), implies that sometimes it could be hard for a researcher to preserve a critical distance to the participant and not to be too overly affected by the behaviour of some elites. In the context of SME owners and entrepreneurs, this can be particularly challenging as by their nature many elites of this type are skilled negotiators who expect to be able to shape and influence social interactions (Artinger et al, 2015;Audretsch and Fiedler, 2023). Critical reflection and discussions within the research team or with senior fellow academics may help preserving a distant position and applying a similar interview style throughout all the interview situations, can be seen as helpful strategies.…”
Section: Elite Perspective On Interviewing Entrepreneursmentioning
confidence: 99%